CyARM: Haptic Sensing Device for Spatial Localization on Basis of Exploration by Arms. (14th December 2009) - Akita, Junichi; komatsu, Takanori; Ito, Kiyohide; Ono, Tetsuo; Okamoto, Makoto
Abstract : We introduce a new type of perception aid device based on user's exploration action, which is named as CyARM (acronym of "Cyber Arm"). The user holds this device in her/his arm, the extension of the arm is controlled by tension in wires, which are attached to her/his body according to the distance to the object. This user interface has unique characteristics that give users the illusion of an imaginary arm that extends to existing objects. The implementations of CyARM and our two experiments to investigate the efficiency and effectiveness of CyARM are described. The results show that we could confirm that CyARM can be used to recognize the presence of an object in front of the user and to measure the relative distance to the object.